Trends in undergraduate economics degrees, 2001–2019. Issue 3 (15th August 2020) - Siegfried, John J.
Abstract: Undergraduate degrees awarded in economics by U.S. colleges and universities were stagnant from 2010 (2009–2010) through 2013, increased rapidly (almost 14 percent) over the 2 years from 2013 through 2015, but have subsequently leveled off from 2016 through 2019.